GAS-DRIVEN FILTER PRESSING IN MAGMAS - Sisson T.W.; Bacon C.R. (My University, 1999)
Most silicic and some mafic magmas expand via second boiling if they crystallize at depths of about 10 km or less. The buildup of gas pressure due to second boiling can be relieved by expulsion of melt out of the region of crystallization, and this process of gas-driven filter pressing assists the crystallization differentiation of magmas. For gas-driven filter pressing to be effective, the region of crystallization must inflate slowly relative to buildup of pressure and expulsion of melt. These conditions are satisfied in undercooled magmatic inclusions and in thin sheets of primitive magma underplating cooler magma reservoirs. Gas-driven filter pressing thereby adds fractionated melt to magma bodies. Gas-driven filter pressing is probably the dominant process by which highly evolved melts segregate from crystal mush to form aplitic dikes in granitic plutons; this process could also account for the production of voluminous, crystal-poor rhyolites.